The Historical Context of Neighborhood Racial Diversity and Crime in Philadelphia, PA - Miller, Jeaneé C. (Journal of contemporary criminal justice, 2022)
Social science theory and research have linked racial diversity to both positive and negative outcomes for communities. Research has also demonstrated that the effects of demographic indicators sometimes vary across space and time. This complex web of results calls for examinations of the spatial and temporal elements at play in this relationship. Using spatial lag models, I analyze the relationship between racial diversity—both as a static measurement and as the 20-year change—and crime in four distinct neighborhood clusters in Philadelphia, PA. I first find evidence of spatial heterogeneity—that racial diversity predicts lower crime rates in one community, but higher crime rates in another. Second, the change in racial diversity influences crime in ways that differ from the static diversity measure. These results provide support for both competing hypotheses regarding the racial diversity–crime connection while also underscoring the role of spatiotemporal contexts in illuminating the dynamism of neighborhood processes.